Analisis Kritis terhadap Kontrak Jual Beli Online dalam Perspektif Fiqh Muamalah - Putri Utami, Pramudita Rizky; Nur Safitri, Via Ayu; Pangesti, Nabila Ayu; Saputro, Alfian Abdi; Rusyda, Muhammad Nasik; Waluyo (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
The development of digital technology has revolutionized the global trading landscape, changing the way we interact with products and services. Buying and selling transactions that were previously limited to physical interactions have now migrated to the digital realm, giving birth to the e-commerce era. This abstract reviews this profound transformation, focusing on the drivers, impact on consumers, and emerging challenges and opportunities. Increased internet accessibility, proliferation of smart devices, and ease of digital payments have been key catalysts in the growth of e-commerce. Consumers can now easily access millions of products from around the world, compare prices, read reviews and make purchases with just a few clicks. The flexibility of time and place in shopping has increased consumer satisfaction and fueled the growth of the industry. However, behind the rapid growth of e-commerce, there are a number of challenges that need to be addressed. Personal data security, risk of fraud, and lack of consumer trust are crucial issues. In addition, immature regulations and the complexity of global supply chains also affect the development of e-commerce. In a broader context, it is important to ensure that e-commerce practices are aligned with ethical values and applicable legal principles. The integration of sharia principles in online transactions, for example, is becoming increasingly relevant in a pluralistic society. The research concludes that e-commerce has fundamentally changed consumer behavior and the business landscape. To achieve sustainable growth, collaboration between businesses, government and society is needed to build a safe, transparent and inclusive e-commerce ecosystem. The development of adequate digital infrastructure, improvement of people's digital literacy, and effective law enforcement are key in realizing this. Keywords : Analysis; Online Buying and Selling; Fiqh Muamal ah